Energy density of the thermal loading and thermal stability of a refractory - Kazakyavichyus, K.A. (Проблемы прочности, 1985)
The present study is devoted to methods of evaluating the thermal stability of a material as it applies to conditions of nonstationary loading under transitional operating regimes of refractories.